Social technology and rescue of native seeds in the Venezuelan Andes Páramo - Lugo Montilla, Iraima; Águas, Carla Ladeira Pimentel (Frontiers in Political Science, 2025)
This study analyzes the recovery and conservation of potato landraces in the Venezuelan Andes Páramo, specifically in the Mérida region. Smallholder potato farmers in the Venezuelan Andes have been actively creating knowledge, processes, and socio-technical artifacts necessary for the recovery of potato seeds and other types of plant genetic resources critical for food and agriculture. This effort has involved diverse socio-technical dynamics, engaging both human and non-human actors, with the support of universities, research institutions, local and national governments, etc. These initiatives counter historical trends, such as the erosion of complex genetic resource systems, genetic resources, the impacts of agricultural modernization, dependency on oil and imported agricultural technologies, and more recent challenges, such as food shortages. Using traditional techniques such as Tinopós—underground caves for seed storage—and social appropriation of technological processes, including genetic improvement, Andean smallholder farmers have successfully rescued ancient potato varieties while developing new ones. Fieldwork conducted in 2019 included a documentary review, thematic analysis, and a technology inventory. The findings reveal a close relationship between the diversity of Andean root and tuber crops, the unique biophysical and climatic conditions of the Páramo, and the traditional knowledge of peasant communities residing in these territories. The study underscores the importance of border relations and cultural translation between different knowledge systems in recovering and conserving native potato seeds. These efforts represent a locally driven initiative to construct social technologies for food sovereignty and sustainable local development.